PENGARUH LEADER MEMBER EXCHANGE (LMX) DAN KOMITMEN ORGANISASI TERHADAP KINERJA DAN KEPUASAN KERJA TENAGA PENDIDIK (GADIK) SEKOLAH POLISI NEGARA KEPOLISIAN DAERAH SUMATERA SELATAN - Romadlona, Ariatna; Alie, Juhaini (JURNAL ILMIAH EDUNOMIKA, 2024)
This research aims to determine the influence of Leader Member Exchange (LMX) and Organizational Commitment on the performance and job satisfaction of Educators (GADIK) at SPN Betung Polda SUMSEL. This research uses the path analysis method with data processing techniques using regression. The test results prove that: 1) The results of this research prove that LMX (Leader Member Exchange) has a positive effect on the performance of Educators (GADIK) at SPN Betung Polda SUMSEL, 2) LMX (Leader Member Exchange) has a positive effect on job satisfaction., 3) organizational commitment has a positive effect on the performance of Educators (GADIK) at SPN Betung Polda SUMSEL, 4) organizational commitment has a positive effect on job satisfaction, 5) LMX (Leader Member Exchange) for Educators (GADIK) at SPN Betung Polda SUMSEL has a positive effect on commitment organization, 6) the results of the analysis of the influence of mediation using path analysis, in testing the influence of LMX (Leader Member Exchange) on job satisfaction with organizational commitment as a mediator, it was concluded that the resulting mediation coefficient had a positive and significant effect, which means that organizational commitment is a mediating factor in the relationship between LMX and job satisfaction, 8) the influence of LMX (Leader Member Exchange) on the performance of Educators (GADIK) with organizational commitment Keywords: Leader Member Exchange (LMX), Organizational Commitment, performance and job satisfaction of Educators (GADIK)